(untitled) (European Journal of Economics, Finance and Business Development, 2025)
This article explores the prospects for the development of corporate governance in Uzbek companies amidst ongoing economic reforms and globalization. As Uzbekistan seeks to enhance its business environment, effective corporate governance practices are essential for fostering investor confidence, ensuring sustainable growth, and improving operational efficiency. The study reviews current governance structures, identifies key challenges such as lack of transparency and accountability, and highlights the importance of aligning with international standards. Ultimately, the article proposes strategic recommendations to advance corporate governance practices in Uzbekistan, emphasizing the need for regulatory reforms, stakeholder engagement, and education.